Geographic atrophy: pathophysiology and current therapeutic strategies - Rajanala, Kalpana; Dotiwala, Farokh; Upadhyay, Arun (Frontiers in Ophthalmology, 2023)
Geographic atrophy (GA) is an advanced stage of age-related macular degeneration (AMD) that leads to gradual and permanent vision loss. GA is characterized by the loss of photoreceptor cells and retinal pigment epithelium (RPE), leading to distinct atrophic patches in the macula, which tends to increase with time. Patients with geographic atrophy often experience a gradual and painless loss of central vision, resulting in difficulty reading, recognizing faces, or performing activities that require detailed vision. The primary risk factor for the development of geographic atrophy is advanced age; however, other risk factors, such as family history, smoking, and certain genetic variations, are also associated with AMD. Diagnosis is usually based on a comprehensive eye examination, including imaging tests such as fundus photography, optical coherence tomography (OCT), and fluorescein angiography. Numerous clinical trials are underway, targeting identified molecular pathways associated with GA that are promising. Recent approvals of Syfovre and Izervay by the FDA for the treatment of GA provide hope to affected patients. Administration of these drugs resulted in slowing the rate of progression of the disease. Though these products provide treatment benefits to the patients, they do not offer a cure for geographic atrophy and are limited in efficacy. Considering these safety concerns and limited treatment benefits, there is still a significant need for therapeutics with improved efficacy, safety profiles, and better patient compliance. This comprehensive review discusses pathophysiology, currently approved products, their limitations, and potential future treatment strategies for GA.